A hybrid catalyst of Pt/CoNiO2 on carbon nanotubes and its synergetic effect towards remarkable ethanol electro-oxidation in alkaline media. Issue 1 (9th November 2017) - Tang, Tingting; Gan, Qiuping; Guo, Xiaohui; Dong, Hailin; Zhang, Jifang; Zhao, Yanchun; Tian, Jianniao; Yang, Xiulin
Abstract : A hybrid catalyst of Pt/CoNiO2 on carbon nanotubes reveals ultrahigh electrocatalytic activity and long-term stability for ethanol oxidation in an alkaline solution. Abstract : Herein, a hybrid catalyst of Pt/CoNiO2 on carbon nanotubes (Pt/CoNiO2 –CNTs) has been successfully synthesized by a facile and cost-effective method, and its crystal structures, chemical valence states, and morphologies have been characterized in detail. CO stripping voltammograms reveal that the adsorbed COads on the active sites of the Pt/CoNiO2 –CNT catalyst is easily oxidized at a lower potential (−0.60 V) as compared to the Pt particles on rGO (−0.35 V) and acid-treated CNTs (−0.36 V). Cyclic voltammograms demonstrate that the designed Pt/CoNiO2 –CNT catalyst possesses an ultrahigh electrocatalytic activity (1136.2 mA mgPt −1 ) for ethanol oxidation, which is 5.1 and 3.0 times higher than that of Pt/rGO (221.6 mA mgPt −1 ) and Pt/CNTs (375.4 mA mgPt −1 ), respectively. The Tafel plot of Pt/CoNiO2 –CNTs is 205 mV dec −1, indicating much faster reaction kinetics than that of the compared catalysts. In addition, the outstanding long-term stability indicates that the designed Pt/CoNiO2 –CNT catalyst exhibits expected application prospects in direct alkaline ethanol fuel cells. Moreover, the catalytic mechanism of the hybrid Pt/CoNiO2 –CNTs has been proposed and discussed via C2 and C1 pathways with respect to the final products for CH3 COO − and CO3 2−, respectively.